Early Prehospital Tranexamic Acid Following Injury Is Associated With a 30-day Survival Benefit: A Secondary Analysis of a Randomized Clinical Trial. Issue 3 (September 2021) - Li, Shimena R.; Guyette, Francis; Brown, Joshua; Zenati, Mazen; Reitz, Katherine M.; Eastridge, Brian; Nirula, Raminder; Vercruysse, Gary A.; O'Keeffe, Terence; Joseph, Bellal; Neal, Matthew D.; Zuckerbraun, Brian S.; et al.
Abstract : Objective: We sought to characterize the timing of administration of prehospital tranexamic acid (TXA) and associated outcome benefits. Background: TXA has been shown to be safe in the prehospital setting post-injury. Methods: We performed a secondary analysis of a recent prehospital randomized TXA clinical trial in injured patients. Those who received prehospital TXA within 1 hour (EARLY) from time of injury were compared to those who received prehospital TXA beyond 1 hour (DELAYED). We included patients with a shock index of >0.9. Primary outcome was 30-day mortality. Kaplan-Meier and Cox Hazard regression were utilized to characterize mortality relationships. Results: EARLY and DELAYED patients had similar demographics, injury characteristics, and shock severity but DELAYED patients had greater prehospital resuscitation requirements and longer prehospital times. Stratified Kaplan-Meier analysis demonstrated significant separation for EARLY patients (N = 238, log-rank chi-square test, 4.99; P = 0.03) with no separation for DELAYED patients (N = 238, log-rank chi-square test, 0.04; P = 0.83). Stratified Cox Hazard regression verified, after controlling for confounders, that EARLY TXA was associated with a 65% lower independent hazard for 30-day mortality [hazard ratio (HR) 0.35, 95% confidence interval (CI) 0.19–0.65, P = 0.001] with no independent survival benefit found in DELAYED patients (HR 1.00, 95% CI 0.63–1.60, P = 0.999). EARLY TXA patients had lower incidence of multiple organ failure and 6-hour and 24-hour transfusion requirements compared to placebo. Conclusions: Administration of prehospital TXA within 1 hour from injury in patients at risk of hemorrhage is associated with 30-day survival benefit, lower incidence of multiple organ failure, and lower transfusion requirements.